E-Commerce untuk Strategi Peningkatan Pendapatan pada Kelompok Pengrajin Pigura â€Kliwonâ€ Kudus - Triyanto, Wiwit Agus; Zuliyati, Zuliyati (SPEED - Sentra Penelitian Engineering dan Edukasi, 2019)
Abstract - Data from the Department of Industry, MSMEs and Cooperatives shows that the Calligraphy Frame Craftsmen are not yet touched by their existence and are not yet recorded, where the craftsmen are one of the handicraft industries producing various kinds of frames for various calligraphy arts which are typical souvenirs for tourists. By using online-based technology through the internet, the sales transaction process can be done more easily and faster because without having to meet with buyers so that it can increase the income obtained by the group of "frame" craftsmen. The results of the research conducted, E-commerce can help the process of selling craft frames by processing orders by buyers online. E-Commerce Design for Revenue Enhancement Strategies in Kudus "Kliwon" Frame Craftsman Group uses the Unified Modeling Language (UML) and the information produced includes product reports and frame categories, buyer reports, and sales reports.Â Keywords: MSMEs, crafts, frames, E-commerce